Legal Gaps in Virtual Currency Investor Protection in Indonesia - Torina, Amalia Salsabila (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study examines the legal gaps governing cryptocurrency investment in Indonesia, identifying issues that arise due to unclear regulations, including potential fraud and risks for investors. By referring to Law No. 7 of 2011, PBI No. 18/40/PBI/2016, and Bappebti Regulation No. 5 of 2019, this article shows how the existence of contradictions in regulations can cause confusion among investors, especially for those who do not have a deep understanding of the legal aspects of investment. In addition, this article recommends various efforts that can be made to improve legal protection for investors, including strengthening regulations through special laws, education and training for investors, and collaboration between the government and related parties. The results of this study are expected to provide insight for policymakers and investors regarding the importance of clear regulations and better protection in virtual currency investment.